2013
DOI: 10.3136/fstr.19.303
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Starch-degrading Enzymes in Rice Grains of Different Cultivars and Elution Behavior during Cooking

Abstract: Rice grains contain starch-degrading enzymes, including α-glucosidases, α-amylases, β-amylase, pullulanase and isoamylases. We investigated the distribution of these enzymes in raw rice grains, and their elution behavior during cooking in Nipponbare and Habutaemochi cultivars. Different distributions and elution behaviors were observed among the different cultivars. These results suggest that differences among cultivars with regard to activation and starch degradation by these enzymes during rice cooking shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…proteins To check the possibility that the anti-barley β-amylase antibody (88-1) cross-reacted with rice β-amylase or other rice proteins, immunoblot analysis of the rice grains extract and extract. This observation was consistent with our previous report, which showed that β-amylase in Nipponbare was hardly detected, throughout the rice grains, with anti-rice β-amylase monoclonal antibody (Tsuyukubo et al, 2013).…”
Section: Cross-reactivity Of Anti-barley β-Amylase Antibody Against Ricesupporting
confidence: 94%
See 1 more Smart Citation
“…proteins To check the possibility that the anti-barley β-amylase antibody (88-1) cross-reacted with rice β-amylase or other rice proteins, immunoblot analysis of the rice grains extract and extract. This observation was consistent with our previous report, which showed that β-amylase in Nipponbare was hardly detected, throughout the rice grains, with anti-rice β-amylase monoclonal antibody (Tsuyukubo et al, 2013).…”
Section: Cross-reactivity Of Anti-barley β-Amylase Antibody Against Ricesupporting
confidence: 94%
“…To understand how crop starch is hydrolyzed during cooking, we focused on β-amylase as the starch-degrading enzyme. Using immunoblot analysis with an antibody against rice β-amylase, we showed that β-amylase was hardly detected in whole rice grains of the rice cultivar Nipponbare (Tsuyukubo et al, 2013). However, the distribution and functions of barley β-amylase during cooking have not been reported especially when barley is cooked with rice (Mugimeshi).…”
Section: Introductionmentioning
confidence: 98%
“…Measured with water (A: no enzyme inhibitors), the peak viscosity for GJ was 1.28 ± 0.05 (×10 3 cP), but when measured with the copper sulfate solution (B: enzyme inhibitors added), the peak viscosity increased to 2.47 ± 0.06 (×10 3 cP), similar to the reports of Shibuya et al (1983) and Shoji and Kurasawa (1988). As α-amylase is an extracellular enzyme in plants from the family Poaceae, it leaches into the water during soaking and cooking, and also acts upon starch in NGJ (Tsuyukubo et al 2013). This appeared to be why the peak viscosity of NGJ+GJ without enzyme inhibitors (A) was lower than that measured with enzyme inhibitors (B).…”
Section: Gelatinization Characteristics Of Rice Gruel Unlike Ngj+ngimentioning
confidence: 67%